Shift Work System Among Hospital Health Workers as a Trigger of Burnout in a Systematic Literature Review - Belinda Putri Berlian; Indah Yuni Astuti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the impact of shift work systems on burnout among hospital healthcare workers using a Systematic Literature Review (SLR) approach guided by the PRISMA method. A total of 55 articles were identified, of which 20 met the inclusion criteria (2021–2025). The review findings indicate that night shifts, long working hours (10–12 hours), and high workloads are the main factors contributing to burnout, characterized by emotional exhaustion, decreased concentration, and physical and mental health disturbances. These conditions not only affect the well-being of healthcare workers but also have implications for the quality of care and patient safety. Therefore, hospital management should design more humane shift policies through regular rotation, limitation of working hours, and organizational support such as counseling services and mental wellness programs.